The theology of Jonathan Edwards : a reappraisal - Cherry, Conrad, 1937- (Indiana University Press, 1990)
" ... The Edwards of Cherry sits for a[n] ... intellectual portrait, done with concepts as colors and with reason as the brush. It is a ... picture ... faithfully and competently drawn."--New York Times Book Review, 1967" ... this is a very good book ... It stresses the integral relationship of heart and mind, intellect and will throughout Edwards ... an important book ... required reading for any student of Edwards."--Church History, 1967